Synthesis and in-vitro antibacterial activity of some alkoxy based N-substituted-5-(furan-2-yl)-phenyl-bis-pyrazolines - Rani, Mamta; Yusuf, Mohamad (European Journal of Chemistry, 2012)
Bis-pyrazoline darivatives (2a-e) built around the alkyl chains of varying length were synthesized in good yield by refluxing bis-chalcones (1a-e) with phenyl hydrazine in CH3COOH and ethanol. The structures of these compounds were elucidated by IR, 1H NMR, 13C NMR, Mass (ESI) spectrometries and their purities were confirmed by elemental analyses. The antibacterial activity of these compounds were evaluated by the disc diffusion assay against two Gram-positive and two Gram-negative bacteria and then the minimum inhibitory concentration of compounds were determined. The compounds 1,4-bis[1-(2-oxyphenyl)-5-(furan-2-yl)-4,5-dihydro-1H-pyrazole] butane (2a) and 1,10-bis[1-(2-oxyphenyl)-5-(furan-2-yl)-4,5-dihydro-1H-pyrazole]decane (2e) are better antibacterial agent as compared to Tetracycline and Gentamicin.